Actual Tasks of Ensuring Harmony of Uzbek Philosophy and Development Strategy - Sharipov Abdukhakimjon Ziyoitdinovich (Researchparks Publishing, 2022)
This article analyzes the role of Uzbek national philosophy in the construction of New Uzbekistan, the foundation of the Third Renaissance, and the social-philosophical aspects of ensuring its connection and coordination with development strategies.